2014
DOI: 10.1155/2014/690752
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Lowering Potentials of Lactic Acid Bacteria Based on Bile-Salt Hydrolase Activity and Effect of Potent Strains on Cholesterol MetabolismIn VitroandIn Vivo

Abstract: This study collected different probiotic isolates from animal and plant sources to evaluate the bile-salt hydrolase activity of probiotics in vitro. The deconjugation potential of bile acid was determined using high-performance liquid chromatography. HepG2 cells were cultured with probiotic strains with high BSH activity. The triglyceride (TG) and apolipoprotein B (apo B) secretion by HepG2 cells were evaluated. Our results show that the BSH activity and bile-acid deconjugation abilities of Pediococcus acidila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 43 publications
5
66
0
2
Order By: Relevance
“…A previous study showed that some Lactobacillus reuteri strains reduced the level of cholesterol from 20.18 to 59.94%, and some Lactobacillus acidophilus strains reduced the level from 49.57 to 55.43% for 24 h ; these results are consistent with the results of the present study. In contrast, another study reported that Lactobacillus casei and Lactobacillus sakei reduced the level of cholesterol by approximately 30% and Pediococcus acidilactici did so by 20% for 24 h . To our knowledge, this is one of the first studies to demonstrate the cholesterol‐reducing activity of LAB strains specifically derived from kefir.…”
Section: Discussionmentioning
confidence: 64%
“…A previous study showed that some Lactobacillus reuteri strains reduced the level of cholesterol from 20.18 to 59.94%, and some Lactobacillus acidophilus strains reduced the level from 49.57 to 55.43% for 24 h ; these results are consistent with the results of the present study. In contrast, another study reported that Lactobacillus casei and Lactobacillus sakei reduced the level of cholesterol by approximately 30% and Pediococcus acidilactici did so by 20% for 24 h . To our knowledge, this is one of the first studies to demonstrate the cholesterol‐reducing activity of LAB strains specifically derived from kefir.…”
Section: Discussionmentioning
confidence: 64%
“…There is also evidence suggesting that alteration of bile acid metabolism by the intestinal microbiota may influence CVD risk by affecting LDL-cholesterol metabolism, vasomotor tone and blood pressure 129,134 . Furthermore, treatment with Bifidobacterium may influence cholesterol metabolism by decreasing serum total cholesterol and LDL-cholesterol concentrations 135 . CDCA treatment has also recently been shown to decrease the LDLreceptor modulator proprotein convertase subtilisin/kexin type 9 (PCSK9) 136 , providing another potentially important mechanism by which BAs may modify cholesterol metabolism.…”
Section: Altered Bile Acid Metabolismmentioning
confidence: 99%
“…Of the different types of probiotics studied, strains from the Lactobacillus and Bifidobacterium species have shown the greatest potential in targeting the risk factors that characterize the metabolic syndrome [12,13,16]. The use of multiple probiotic strains simultaneously has also been suggested to bring together the many benefits associated with each individual probiotic [17][18][19].…”
Section: Introductionmentioning
confidence: 99%